ANALISIS SENGKETA PENARIKAN OBJEK JAMINAN FIDUSIA SECARA PAKSA (STUDI KASUS PUTUSAN NO.113/PDT.G/2018/PN.BTM) - Jordi Living Gosan; Hanafi Tanawijaya (Jurnal Hukum Adigama, 2022)
Fiduciary guarantee is a creditor's loan agreement to the debtor that involves guarantee. When thedebtor or fiduciary giver breaks his promise or does not fulfill his performance on time to the creditor,the execution of the fiduciary guarantee will be applied, namely the withdrawal of the object that hasbeen agreed upon. Eddy Lim (plaintif ) sued PT Maybank Indonesia Finance (defendant) because heconsidered that his actions in withdrawing and executing the object of fiduciary security, namely oneunit of a four-wheeled vehicle with the Datsun Co-Panca brand, were not in accordance with theexisting rules and regulations and should only be carried out by the court through an auction, so thatthe plaintif feels that he has been harmed. The Plaintif and the Defendant have made a financingagreement with a fiduciary transfer of property rights, namely the plaintif will pay in installments withan installment payment agreement period of 36 months, starting from November 2014 to October2017. However, the plaintif did not make a deposit for 3 months, therefore the defendant pull objects.However, the court's decision rejected the plaintif 's application due to the non-fulfillment of relativecompetence and an error in persona. The purpose of this study is to know and understand the law ofguarantees in disputes over the forcible withdrawal of fiduciary objects. The types of data used areprimary data and secondary data.